Kaip Juozą Jurginį 1961 metais Maskva „šukavo" - Vyšniauskas, Arūnas (Lietuvos istorijos studijos, 2010)
This study discusses the secret Resolution of the Central Committee of the Communist Party of the Soviet Union (CPSU) on 16 August 1961. The Resolution was named "Serious errors in the textbook of J. Jurginis' 'History of Lithuanian SSR' and 'Readingsbook for the History of Lithuanian SSR'." The issue deals with decision-making in the context of Kremlin's politics of history, historical background, and reasons. From the Kremlin's point of view, J. Jurginis' educational literature could have led to complications in the entire history of the USSR and have had a potential negative impact on other Soviet republics. A historical periodization according to Lithuanian statehood phases from Grand Duchy of Lithuania until Soviet Lithuania was a particular concern raised by Moscow in Jurginis' textbook. The Soviet government in Moscow found it very difficult to coordinate the old history of all 15 Soviet republics with various periodization phases in their schoolbooks. In that case, the General schoolbook of the USSR (from the ancient kingdom of Urartu until Contemporary history) could have lost its significance. This is why Moscow reacted sharply, but with discretion, without abandoning the idea of having separate history schoolbooks for Soviet republics. Moscow gave clear directives for Lithuanian historians to adapt the history of Lithuania to the general historical conception of the Soviet Union, which was a substantially Russocentric doctrine. This was adopted with the release of a new textbook "History of the Lithuanian SSR" and a new Readingsbook in 1962. The research made on this issue was carried out using new archival material from the Lithuanian Special Archives, the old textbooks, newspapers, and other historical materials from Soviet times. The Soviet Union is considered as a kind of continental empire, which indicated directives from Moscow for history teaching in all Soviet republics. The communist ideologists' old fears had not been without reason, as a new reality showed schoolbook evolution in the post-Soviet space. Various collisions and significant historian conflicts started on this front. These confrontations could be sometimes called the "history wars" between neighboring countries. The new trends after the collapse of the Soviet empire enable a better understanding of the old unified Khrushchev era history schoolbooks. It is assumed that the Resolution of the Central Committee of the CPSU on 16 August 1961 played a crucial normative role on an All-Soviet-Union level. Moscow required Soviet republics to present their own history only as a complement to the overall set of Soviet history curriculum and textbooks.